The effects of inactivated SARS‐CoV‐2 vaccination and subsequent infection of pregnant mice on the behaviors of offspring - Kaili Lin; Meixuan Liu; Lu Sun; Hongwei Qiao; Shunyi Wang; Sidan Pan; Hanjun Fu; Jingzhu Wang; Qiang Wei; Hong Gao (Animal Models and Experimental Medicine, 2022)
Abstract The mass inoculation of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines to induce herd immunity is one of the most effective measures we can deploy in the fight against coronavirus disease 2019 (COVID‐19). Pregnant women are prone to a higher risk of COVID‐19, and maternal infection is a risk factor for a range of neurological disorders leading to abnormal behavior in adulthood. However, there are limited clinical data to support whether vaccination or infection post‐immunization in pregnant women can affect the behavioral cognition of fetuses in adulthood. In this study, human angiotensin‐converting enzyme 2 pregnant mice (F0 generation) were immunized with CoronaVac and then infected with SARS‐CoV‐2. Subsequently, we analyzed the behavioral cognition of their adult offspring (F1 generation) using the open‐field test and Morris water maze test. The adult F1 generation did not exhibit any impairments in spontaneous locomotor activity or spatial reference memory.